Characterization of TLR expression in Staphylococcus aureus induced mastitis in mice model by probe based real time PCR - MITRA, SUSWETA DAS; GHOSH, SANKAR KUMAR; KRISHNAMOORTHY, P; CHAKRABORTY, ANAMIKA; C, NIMITA VENUGOPAL; ROY, MANISHA; SHOME, BIBEK RANJAN; RAHMAN, HABIBUR (The Indian Journal of Animal Sciences, 2014)
Staphylococcus aureus infection of the bovine mammary gland can result in a spectrum of clinical outcomes ranging from acute to chronic and subclinical. A molecular understanding of the principles causing this is particularly important to eventually develop innovative strategies for prevention and treatment in mastitis. The present study characterized the temporal (2, 4, 8, 12, 24 and 48h) expression of 5 important toll like receptors (TLR 2, TLR 4, TLR 9, TLR 11 and TLR 12) induced by S. aureus intramammary inoculation (IMI) in established mice model employing probe based real time PCR (RT-PCR). S. aureus challenge provoked transcriptional expression of each of the 5 TLRs in a temporal manner with maximum expression at 8 h after IMI. S. aureus maximally altered the mRNA concentration of TLR 9 and TLR 12 (> 5 fold) over the PBS control. We found TLR2 to be weakly (1- to 2- fold) regulated by the S. aureus challenge in this study. This study emphasized the contribution of other TLRs besides the most commonly studied TLR 2 and TLR 4 in activating immune response by switching on several receptors mediated signalling cascades. This study sheds light into the diverse pathogen recognition receptor (PRR) mediated mechanisms involved in host pathogen interaction.